MEDIA SOSIAL SEBAGAI SARANA KEBEBASAN BERPENDAPAT BAGI PENGANUT ATEIS MENURUT UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Setiawan, Andi (POLITEKNIK LP3I JAKARTA, 2021)
Social media is a strategic means of sharing information, opinions and expressing attitudes for netizens, including expressing themselves as atheists. Being an atheist is a trend for some people right now. The purpose of this research is to find out whether expressing the expression of being atheist through social media can violate the Information and Electronic Transactions Law. The right to freedom of expression is regulated in the 1945 Constitution and the ITE Law. Not a few netizens have been caught up in the ITE Law regarding their careless comments. The acknowledgment of being an atheist as long as it does not insult and desecrate ethnicity, religion, race and between groups is an expression of the thoughts of these citizens who are poured out through social media. The category of this research is library research by emphasizing the concept of law in books, namely law as stated in statutory regulations or law as a norm in the form of guidelines for community behavior that is considered appropriate or not. With Pancasila as the grundnorm of the Indonesian nation, the state protects all religions, beliefs and adherents from defamation and humiliation.Key words: The acknowledgment of being an atheist. Social Media. ITE law.